LIFE EXPERIENCES AND WORKS OF MUHAMMAD AMINKHOJA MUKYMI - Mamayusupova, Shakhina Ulugbek kizi (Educational Research in Universal Sciences, 2023)
This article describes the life and work of Muhammad Aminkhoja Mukymi. The truths about his way of life and creativity, his attitude to the people around him, about how much he valued science. Socio-economic development of the period in which he lived. About the level of justice of the population, excerpts from the works of Tanobchilar are quoted. It was further explained that the population was in a difficult period, that most of the officials were held by their relatives, and all their incomes were exhausted. The difficulties of the resident’s lifestyle are described